Cryptococcal Meningitis in an HIV-Negative Puerperal Woman. (26th May 2021) - Robalo Nunes, Tomás; Pires, Helena; Alves, Liliana; Guerra, Ana; Boavida, Susana; Brito, Ana; Marques, Inês; Marques, Nuno
Abstract : Cryptococcal meningitis is a common opportunistic infection in HIV-infected patients and other immunocompromised people. Pregnancy, which is a state of relative immunosuppression, can also be a risk factor for the development of cryptococcal meningitis. We report a clinical case of a 41-year-old woman who developed a severe meningeal syndrome after an otherwise normal pregnancy. Cerebrospinal fluid (CSF) cytochemical analysis presented hypoglycorrhachia, high protein levels, and pleocytosis. Cryptococcal antigen tested positive in serum and CSF, and Cryptococcus neoformans was identified in the CSF culture . The diagnosis of cryptococcal meningitis was confirmed, and antifungal induction therapy was started with liposomal amphotericin B and flucytosine. After clinical improvement, induction therapy was discontinued, and the patient was discharged under maintenance therapy with fluconazole. While under antifungal maintenance therapy, the patient presented worsening of symptoms and a new brain magnetic resonance showed the development of multiple cryptococcoma. Despite sterile CSF cultures, there was a deterioration of the cytochemical parameters. The diagnosis of immune reconstitution inflammatory syndrome was assumed, and after initiation of corticotherapy, the patient improved considerably. This is a rare case of cryptococcal meningitis in a puerperal woman with a challenging management.